Guidebook to effective speech and public speaking - Aguinaldo, Milagros M.; Besacruz, Flora C. (Quezon City, Philippines : MMA Publications, 2002)
The book has for its essential objectives to inform on how to become engaging in speech and to improve the image of the speaker. Very specific in its instructions with hints for a responsive conversation.
Types of Speech -- The Impromptu Talk -- The Extemporaneous Talk -- The Memorized Speech -- Speaking from a Manuscript -- Speaking with notes -- Guide to Speech Delivery -- The Emotions of the Audience -- Aspects of Delivery -- Physical Aspects -- Cardinal Reminders for an Effective Speech and Public Speaking -- Personality -- Personal Grooming -- Attitude -- Other factor that make up effective speech -- Integrity -- Training and Critical Thinking -- Technique -- Physical Properties of Voice -- Voice -- Gesture -- Visual Aids -- Language -- Message -- Stage presence and audience impact flow -- How to become a good emcee -- The interview -- The announcement -- Radio and Televising Talk -- Gentle reminders to consider -- Basic types of speeches -- The informative S\speech -- Speech to persuade -- Speech to entertain -- The Argumentation Speech.
Includes bibliographical references.
Keywords: PUBLIC SPEAKING -- SPEECHES